Feminism and the Birth of Sexual Crime as International Crime and the Challenge of Its Implementation in the Future - Zunnuraeni, Zunnuraeni; Tarigan, Rehulina; Nurbani, Erlies Septiana; Jannah, Aisyah Wardatul (UI Scholars Hub, 2022)
The existence of international sexual crimes in international court jurisprudence and the international law instruments have evolve as an extensive crime from the abundance crime of outrages upon personal dignity, yet still have to front some challenges to attain triumph in its enforcement. This article aims to observe the sexual crimes as international crime in some aspect, namely, its development and the contribution of feminism, the challenges on the law enforcement against international criminal law and the position of feminism in addressing those challenges. In every stage of sexual crimes evolution as international crimes, feminism hold important contribution. Their impact made up in building international community opinion, sounding and criticizing, and engage in making court decisions through judges with a feminism paradigm. The success in ICTY and ICTR landmark decision and the determination of extensive sexual crimes in Rome Statue, renounce some obstacle which might eliminated by feminism ideas and movement. Once again through pressures and criticisms, awareness of sexual crimes shall increase so that come the incriminating in the completion of sexual crimes cases before international court. The role of feminism is also vital through the presence of prosecutors and judges with a feminism paradigm so that, as before, landmark decisions as produced in the ICTY and ICTR can be issued at the ICC.